Effects of Different Training Methods on Open-Skill and Closed-Skill Agility in Basketball Players: A Systematic Review and Meta-Analysis - Mingxiang Zhang; Feng Li; Jiao Jiao; Wei Liang; Miguel-Angel Gomez; Aaron T. Scanlan (Sports Medicine - Open)
Abstract Background Open-skill and closed-skill agility attributes are pivotal for achieving success in basketball. However, systematic synthesis of evidence regarding the effectiveness of different basketball-specific training methods on agility performance is lacking among basketball players in the literature. Consequently, this systematic review with meta-analysis aimed to evaluate the effectiveness of prominent training methods in improving open-skill and closed-skill agility in basketball players. Methods Using keywords related to ‘basketball’, ‘agility’, and ‘training’, we searched for experimental studies in PubMed, Web of Science, and EBSCOhost databases that were published in the last decade (between January 2013 and September 2023). The included training methods were categorized into five groups, including reaction training (RT), speed training (SpT), strength and balance training (SBT), plyometric training (PT), and stretching training (StrT). The effects of training methods were summarized using standardized mean differences (SMD) with 95% confidence intervals in R software. Results A total of 29 studies met the inclusion criteria, comprising 42 separate effects. Studies only assessed the effects of different training methods on closed-skill agility performance, with no open-skill agility assessments used. Improvements in closed-skill agility were apparent between pre-and post-training intervention with most training methods including a large effect for RT [SMD = 0.86, 95% CI (0.53, 1.19)], medium effects for PT [SMD = 0.62, 95%CI (0.38, 0.86)] and SBT [SMD = 0.59, 95%CI (0.13, 1.05)], and a small effect for SpT [SMD = 0.43, 95%CI (0.13, 0.74)]. While no effect for StrT [SMD = 0, 95%CI (-0.98, 0.98)] was apparent, only one study examined this training method. Conclusions RT appears to be the most effective method for developing closed-skill agility among basketball players, particularly when implemented in small-sided games. SBT and PT also appear impactful in developing closed-skill agility to similar extents. SpT appears to benefit closed-skill agility to a minor extent with limited research examining the effectiveness of StrT on agility among basketball players. Surprisingly, no studies have incorporated open-skill agility tests when assessing the effectiveness of training methods, which is essential to address in future research. Outcomes from this review provide guidance to basketball coaches and performance staff for selecting training methods that optimize closed-skill agility performance in their players.